Utility of preoperative imaging in evaluating colorectal liver metastases declines over time - Yang, Simon (Blackwell Publishing Ltd, 2010)
OBJECTIVES: Reports on the sensitivity and accuracy of contrast-enhanced helical computed tomography (HCT) in the preoperative evaluation of colorectal liver metastases (CLM) have been conflicting. Few studies have controlled for and reported on the time interval between HCT and eventual surgery. METHODS: A multi-institution, retrospective review of consecutive patients who underwent hepatic resection for CLM from January 1999 to September 2004 was conducted. Data regarding lesion characteristics and resectability were extracted from radiology reports, operative findings and histopathological records. Findings in HCT were evaluated according to their sensitivity for detecting CLM and ability to predict resectability. RESULTS: A total of 217 consecutive patients who underwent hepatic resection for CLM were identified. The overall sensitivity of HCT for detection of CLM was 83.2%. Prolonged time between imaging and surgery was a negative predictor for HCT sensitivity in univariate and multivariate analysis (P < 0.001). In predicting resectability, preoperative HCT was accurate 77.0% of the time. The time interval to surgery was negatively correlated with HCT prediction accuracy in univariate and multivariate analyses (P < 0.001). CONCLUSIONS: The utility of HCT as a preoperative tool to evaluate CLM is inversely proportional to the time interval between imaging and surgery. This may explain conflicting reports of the accuracy of HCT in the current literature.